Implementasi Pemeriksaan Antropometrik dan Pemberian Makanan Bahan Dasar Ikan Laut pada Anak Beresiko Stunting di Kelurahan Matani II Kota Tomohon - Martha Debora Korompis (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2024)
One of the efforts to overcome stunting is by providing additional food with sea fish and carrying out anthropometric measurements. In order to evaluate this, a community service program is needed as a form of program implementation. The aim is that through the implementation program the effectiveness of anthropometric measurements and feeding will be known. The community service method used is a pilot method. The steps include studying phenomena that exist in society, identifying problems based on previous research, prioritizing problems and determining locations, then implementing programs, evaluating programs and preparing reports. The target population is children under 5 years old in Manani II Village, Tomohon. The instruments used were questionnaires for demographic data and anthropometric measurements for primary data. Data was processed univariately with descriptive analysis. Community service results show that the number of toddlers who are underweight and whose height is less than normal for their age is 4 children (16.6%), and there are still mothers who have toddlers who don't understand the benefits of food made from sea fish as a nutritious food. (17.4), and those who are still unsure are 34.8%. In conclusion, anthropometric measurements and the provision of sea fish can be concrete examples of effective community service methods in overcoming stunting in society